Effects of drought and meteorological forcing on carbon and water fluxes in Nordic forests during the dry summer of 2018. (26th October 2020) - Lindroth, Anders; Holst, Jutta; Linderson, Maj-Lena; Aurela, Mika; Biermann, Tobias; Heliasz, Michal; Chi, Jinshu; Ibrom, Andreas; Kolari, Pasi; Klemedtsson, Leif; Krasnova, Alisa; Laurila, Tuomas; et al.
Abstract : The Nordic region was subjected to severe drought in 2018 with a particularly long-lasting and large soil water deficit in Denmark, Southern Sweden and Estonia. Here, we analyse the impact of the drought on carbon and water fluxes in 11 forest ecosystems of different composition: spruce, pine, mixed and deciduous. We assess the impact of drought on fluxes by estimating the difference (anomaly) between year 2018 and a reference year without drought. Unexpectedly, the evaporation was only slightly reduced during 2018 compared to the reference year at two sites while it increased or was nearly unchanged at all other sites. This occurred under a 40 to 60% reduction in mean surface conductance and the concurrent increase in evaporative demand due to the warm and dry weather. The anomaly in the net ecosystem productivity (NEP) was 93% explained by a multilinear regression with the anomaly in heterotrophic respiration and the relative precipitation deficit as independent variables. Most of the variation (77%) was explained by the heterotrophic component. Six out of 11 forests reduced their annual NEP with more than 50 g C m −2 yr −1 during 2018 as compared to the reference year. The NEP anomaly ranged between −389 and +74 g C m −2 yr −1 with a median value of −59 g C m −2 yr −1 . This article is part of the theme issue 'Impacts of the 2018 severe drought and heatwave in Europe: from site to continental scale'.